Local immunoglobulin production in nasal polyposis is modulated by superantigens - Van Zele, T.; Gevaert, P.; Holtappels, G.; Van Cauwenberge, P.; Bachert, C. (Clinical and experimental allergy, 2007)
Summary Background Chronic rhinosinusitis (CRS) with nasal polyps (NP) represents a persistent inflammation often characterized by local hyper‐immunoglobulinaemia and the presence of specific IgE to Staphylococcus aureus enterotoxins (SAEs). We aimed to study the systemic and local production of Igs in relation to plasma cells, B cells and specific IgE to SAEs. Methods Concentrations of IgE, IgG, IgM, IgA, IgG subclasses and specific IgE to SAE were determined on tissue homogenates and serum from 15 CRS patients with NP, 15 CRS without NP and 10 control patients. Tissue cryo‐sections were stained for CD19, CD20 and CD138 to demonstrate B and plasma cells. Results IgA, IgG and IgE concentrations were significantly higher in tissue homogenates, but not in serum, of NP compared with CRS and control subjects. NP with specific IgE to SAEs had significantly higher concentrations of IgG and IgE, and also showed a significantly higher fraction of IgG4 (P=0.003) and a lower fraction of IgG2 (P=0.04) than those without specific IgE production. Furthermore, naïve CD19+ B cell and plasma cell counts (CD138+) were significantly higher in NP tissue compared with controls or CRS. Conclusions The difference in IgE, IgG and IgA expression between NP tissue and serum, supported by increased numbers of plasma cells, suggests a local production of these Igs in NP in response to a chronic microbial trigger. The local immune response to SAE is associated with a further increased production of IgE and IgG, and a shift in IgG subclasses.